2022
DOI: 10.3390/polym14153132
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Destructive and Nondestructive Analysis for GGBS Based Geopolymer Concrete and Its Statistical Analysis

Abstract: Geopolymer is the alternative to current construction material trends. In this paper, an attempt is made to produce a sustainable construction composite material using geopolymer. Ground granulated blast furnace slag (GGBS)-based geopolymer concrete was prepared and tested for different alkaline to binder ratios (A/B). The effect of various temperatures on compressive strength properties was assessed. The cubes were exposed to temperature ranging from 50 to 70 °C for a duration ranging from 2 to 10 h, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…At temperatures of 0~50 °C, the surface tension and contact angle of water change little in concrete; therefore, the temperature has less influence on the water absorption when the water is in a liquid and flowing condition. However, the pore distribution and pore size of concrete will change with the hydrophobic admixture [ 11 , 12 , 13 ], which causes water adsorption process variation with the concentration of TIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At temperatures of 0~50 °C, the surface tension and contact angle of water change little in concrete; therefore, the temperature has less influence on the water absorption when the water is in a liquid and flowing condition. However, the pore distribution and pore size of concrete will change with the hydrophobic admixture [ 11 , 12 , 13 ], which causes water adsorption process variation with the concentration of TIA.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the improvement of the permeability of concrete is mainly achieved by improving the compactness of cement-based materials and optimizing the pore structure by reducing the water/cement ratio, and the addition of auxiliary cement-based materials or nanoparticles [ 10 , 11 , 12 , 13 ]. However, there are still some problems with these common methods, such as increasing the shrinkage of concrete, affecting workability, and making dispersion difficult in highly aggressive environments.…”
Section: Introductionmentioning
confidence: 99%
“…These new hydration zeolitic compounds are durable at elevated temperatures [23]. Shilar et al [24] concluded that the hydration rate of ground granulated blast furnace slag decreases when the molarity of the alkali activator increases from 8 M to 12 M. The optimal hydration temperature was found to be 70 • C. In another study [25], the best ratio of sodium silicate solution to precursor made from metakaolin and fly ash was 0.7. In this case, the highest compressive strength reached 40.2 MPa.…”
Section: Introductionmentioning
confidence: 98%
“…For example, in works [11][12][13][14], the authors developed various compositions of geopolymer concretes, where fly ash was used as an aluminosilicate component, and the strengths of the composites varied from 15 MPa to 70 MPa. In studies [15][16][17], various types of slag were used as a binder, and the strength of geopolymer composites varied from 40 MPa to 70 MPa. Also, in addition to the above types of aluminosilicate components, metakaolin, microsilica and ground waste from concrete and brick waste are used for the production of geopolymer composites [18][19][20].…”
Section: Introductionmentioning
confidence: 99%